Psoriatic Disease and Tuberculosis Nowadays. (8th May 2012) - Balato, Nicola; Di Costanzo, Luisa; Ayala, Fabio; Balato, Anna; Sanduzzi, Alessandro; Bocchino, Marialuisa
Abstract : Psoriasis is a chronic, relapsing and remitting inflammatory skin and joint disease that has a prevalence of 2-3% in the world's population, whereas of 1–2% in Europe. The traditional concept of psoriasis as the "healthy people's" disease has been recently revised because of ever-increasing reports of associations with various pathological conditions (hypertension, Crohn's disease, type II diabetes mellitus, obesity, dyslipidemia, metabolic syndrome, infectious conditions). Particularly, advances in psoriasis therapies have introduced biologic agents. All the tumor necrosis factor-alpha inhibitors are associated with an increased risk of developing active disease in patients with latent tuberculosis infection, because of TNF- α key role against Mycobacterium tuberculosis . For this reason, exclusion of active tuberculosis and treatment of latent tuberculosis infection are clinical imperatives prior to starting this therapy. Moreover active surveillance for a history of untreated or partially treated tuberculosis or latent form has already been shown to be effective in reducing the number of incident tuberculosis cases.